AG-FE3O4 HYBRID NANOFLUID DYNAMICS: EXPLORING SLIP AND MAGNETIC EFFECTS ON THE FLOW OVER EXPONENTIALLY ELONGATED/CONTRACTED SURFACE - Rahimah Jusoh; Zulkhibri Ismail; Mikhail Sheremet; Nooraini Zainuddin; Mohd Hisyam Ariff (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2026)
This study explores the unique advantages of hybrid nanofluids, known for their exceptional ability to boost heat transfer efficiency, making them ideal for advanced thermal applications. The objective is to assess the impact of slip and magnetic field on the velocity and temperature profiles over an exponentially elongated/contracted surface. Through the application of an appropriate similarity transformation, the governing equations for energy, momentum, and mass are converted into ordinary differential equations. These resulting equations are subsequently solved numerically via the bvp4c function in MATLAB. Results imply that magnetic fields decelerate the fluid while thickening the thermal boundary layer due to the Lorentz force. Increased viscous dissipation elevates temperature levels, while surface elongation promotes convective heat transfer. In contrast, surface contraction and velocity slip suppresses thermal transport by limiting momentum exchange. Thermal slip further reduces surface heat flux These findings underscore both the novelty and practical potential of Ag–Fe₃O₄ hybrid nanofluids in enhancing performance across thermal regulation systems, such as energy-efficient cooling devices, biomedical heat exchangers, and industrial applications.